An appraisal of the geologic structure beneath the ikogosi warm spring in south-western nigeria using integrated surface geophysical methods (2011)
An integrated surface geophysical investigation involving resistivity and magnetic methods was carried out in the immediate vicinity of the Ikogosi warm spring situated in south-western Nigeria with a view to delineating its subsurface geological sequence and evaluating the structural setting beneath the warmspring. Total field magnetic measurements and vertical electrical sounding (VES) data were acquired along five N-S traverses. Magnetic and VES data interpretation involved inverse modelling. The inverse magnetic models delineated fractured quartzite/faulted areas within fresh massive quartzite at varying depths and beneath all traverses. The geoelectrical sections developed from VESinterpretation results also delineated a subsurface sequence consisting of a topsoil/weathered layer, fresh quartzite, fractured/faulted quartzite and fresh quartzite bedrock. It was deduced that the fractured/faulted quartzite may have acted as conduit for the movement of warm groundwater from profound depths to the surface while the spring outlet was located on a geological interface  (lineament).